Qualitative Analysis and Study of Pb, Cd, Cr and Zn in Cultivated Shrub and Non-Shrub Cucumber (Cucumis sativus L.) of Sari, Iran - Norouzi , M.; Ashrafi, F. (Asian Journal of Chemistry, 2010)
The analysis of the metal ion were performed on the cultivated cucumber in Mazandaran province. The samples were taken from 10 regions and 5 sample from each plant. The samples were washed, dried and then with dry by aching method. The results from this research based on statistical analysis ANOVA evaluation, which showed a meaningful relation between the amount of lead and regions (p < 0.05) and also compared between these mean numbers shows that in Eastern station lead has the highest amount with average 5.152 ppm non-shrub and 6.281 ppm in syrup. Regarding other metals, the results are below standard with the respect to the obtained results.